Fate of Pharmaceuticals in a Submerged Membrane Bioreactor Treating Hospital Wastewater - Tiwari, Bhagyashree; Ouarda, Yassine; Drogui, Patrick; Tyagi, Rajeshwar D.; Vaudreuil, Marc Antoine; Sauvé, Sébastien; Buelna, Gerardo; Dubé, Rino (Frontiers in Water, 2021)
The fate of twelve pharmaceutical pollutants was investigated to understand their removal mechanism during hospital wastewater (HWW) treatment in submerged membrane bioreactor (SMBR). High concentrations of anti-depressant (venlafaxine and desvenlafaxine), analgesic (ibuprofen and hydroxy-ibuprofen), and caffeine were detected in the HWW during the entire study period. The SMBR showed high removal > 70% of antibiotics (sulfamethoxazole and clarithromycin), beta-blocker (acebutolol), hormone (estrone), and caffeine via biodegradation. The partial degradation of diclofenac, venlafaxine, and desvenlafaxine in SMBR indicates the growth promoter or agent requirement, which could facilitate the metabolism and co-metabolism of these pharmaceuticals by microorganisms. The study demonstrated that the major removal mechanism of pharmaceuticals in SMBR at optimized treatment conditions was biodegradation for the majority of examined pharmaceuticals. The assessment of SMBR performance at the low temperature of 15 and 10 °C resulted in the drop of biodegradation efficiency of SMBR, affecting overall pharmaceuticals removal.